EFFECT OF LIBRARY SERVICES ON STUDENTS’ ACADEMIC ACHIEVEMENT IN SECONDARY SCHOOL AT BANKURA DISTRICT IN WEST BENGAL - Bagdi , Amit (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2022)
A library can be defined as a location where information materials in various formats are methodically gathered, arranged, kept, maintained, and made available to users when necessary to suit their information needs. This study’s purpose is to examine how library services affect students’ academic performance in secondary schools in West Bengal’s Bankura. Researcher used survey method and descriptive statistics for conducting this research work. Researcher find out and conclude that is significant difference between library service and academic achievement of secondary level students Ho1 in Bankura District and Ho2 is finding that negative relationship observed between library service and academic achievement of secondary level of students.